The Influence of Context Specificity on Entrepreneurial Behavior Modalities - Lidija Mitrašević; Dejan Sekulić (Proceedings of Faculty of Economics Brcko, 2021)
The pronounced multidimensionality and diversity of entrepreneurial behavior make it impossible to explain it on basis of a single, universally applicable model. Understanding the characteristics, dynamics, uniqueness, and limitations of different manifestations of entrepreneurial activity requires consideration of the specifics of the context in which it manifests itself. Based on a systematic review of the relevant literature, the paper defines and analyzes the role of context in researching the phenomenon of entrepreneurship, and then proposes a nomenclature of context dimensions in order to indicate the need to apply different perspectives. This is extremely important when defining problems, subjects and choosing the approach to research, as well as for generating alternative explanations and identifying unnoticed manifestations of entrepreneurship. After presenting the theoretical and pragmatic implications of the interdependence of entrepreneurial activities and different dimensions of the context, recommendations for future research are given.
Keywords: L26; 330; entrepreneurial behaviour; entrepreneurial context; dimensions